LATE ALBIAN RADIOLARIANS AND FORAMINIFERS FROM THE MAR'INO SECTION (OUTSKIRTS OF SIMFEROPOL, CRIMEA): TAXONOMIC COMPOSITION AND STRATIGRAPHIC POSITION - Gorbachik T.N.; Kazintsova L.I. (My University, 1998)
The first study on taxonomic composition of radiolarians from the upper Albian deposits of Crimea showed that they represent 48 taxa, among which 15 genera and 29 species are classed with spumellarians, and 14 genera and 19 species with nassellarians. The discovered community of radiolarians is termed as an Orbiculiforma nevadaensis-Dictyomitra konachkendensis assemblage. It includes species common with those from coeval radiolarian assemblages of the Russian platform, Ukraine, Caucasus, and Sakhalin. The radiolarians in question coexist with planktonic and benthonic foraminifers indicating the late Albian age of their host rocks.
Keywords: Albian; Mesozoic::Cretaceous::Lower::Albian; Мезозой::Меловая::Нижний::Альбский